OZONE AND OZONE PRECURSORS IN URBAN ATMOSPHERE: OZONE AND OZONE PRECURSORS IN URBAN ATMOSPHERE - Chuturkova , Rozalina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Monitoring of atmospheric air at an urban background station in the city of Varna, Bulgaria between 2007 and 2014 to evaluate the levels of the secondary pollutants О3 and its precursors – NO, NO2, NMHC and CO. Annual, monthly and diurnal variations were studied. The results show that О3 and the precursors do not exceed the norms that threaten human health. As compared with the start of the monitoring, the О3 concentrations have risen from 32.22 to 52.04 µg/m3 and the differences have high statistical significance (0.025 ≤ Р ≤ 0.05). The maximum concentrations of the secondary pollutant О3 are achieved several hours after the peak precursor levels. Measures are proposed for reduction of the emissions of the О3 precursors with the aim to reduce the concentrations of the secondary pollutant in the lower atmosphere.